A contribution to the study of the cortinarioid mycoflora of New Zealand, VII. Issue 3 (2nd July 2016) - Soop, Karl
ABSTRACT: Fourteen new species are described from New Zealand, Cortinarius amblyonis, Cortinarius chrysoconius, Cortinarius cremeorufus, Cortinarius cypripedii, Cortinarius dulcamarus, Cortinarius entheosus, Cortinarius lachanus, Cortinarius mycenarum, Cortinarius mysoides, Cortinarius psilomorphus, Cortinarius trichocarpus, Cortinarius urbiculus, Cortinarius vitreofulvus and Cortinarius xenosmatoides . Also two new sections, Cortinarius sect. Cremeolinae and Cortina-rius sect. Cycnei, are proposed, and a new form of Cortinarius lubricanescens is described. The Patagonian taxon Cortinarius rapaceus var. luridus is raised to species rank under the replacement name Cortinarius austrorapaceus .